Genetic and Functional Dissection of the Role of Individual 5-HT(2) Receptors as Entry Receptors for JC Polyomavirus - Assetta, Benedetta (Cell Rep, 2019)
JC polyomavirus (JCPyV) is a ubiquitous human pathogen that causes progressive multifocal leukoencephalopathy (PML). The entry receptors for JCPyV belong to the 5-hydroxytryptamine 2 receptor (5-HT(2)R) family, but how individual members of the family function to facilitate infection is not known. We used proximity ligation assay (PLA) to determine that JCPyV interacts with each of the 5-HT(2) receptors (5-HT(2)Rs) in a narrow window of time during entry. We used CRISPR-Cas9 to randomly introduce stop codons in the gene for each receptor and discovered that the second intracellular loop of each was necessary for infection. This loop contains a motif possibly involved in receptor internalization by β-arrestin. Mutation of this motif and small interfering RNA (siRNA) knockdown of β-arrestin recapitulated the results of our CRISPR-Cas9 screen, showing that this motif is critical. Our results have implications for the role these receptors play in virus infection and for their normal functioning as receptors for serotonin.